The feasibility of hepatic resections using a bipolar radiofrequency device (Habib®) - Civil, Osman; Kement, Metin; Okkabaz, Nuri; Haksal, Mustafa; Gezen, Cem; Öncel, Mustafa (Springer, 2015)
The bipolar radiofrequency device (HabibA (R)) has been recently introduced in order to reduce intraoperative bleeding for a safe hepatic resection as an alternative to the conventional tools. However, indications, perioperative findings, and outcome of the device for hepatic resections remain and deserve to be analyzed. The current study aims to analyze the feasibility of the bipolar radiofrequency device (HabibA (R)) for hepatic resections. Information of the patients that underwent hepatic resection using with the HabibA (R) device between 2007 and 2011 was abstracted. Patient, disease, and operation-related findings and perioperative data were investigated. A total of 71 cases (38 [53.5 %] males, mean age was 56.8 A +/- 11.9) were analyzed. Metastatic disease (n = 55; 77.5 %) was the leading indication followed by primary liver and biliary malignancies (n = 7; 9.9 %), hemangioma (n = 5; 7 %), hydatid disease (n = 3; 2.8 %), and hepatic gunshot trauma (n = 1; 1.4 %). Metastasectomy was the most commonly performed procedure (n = 31; 56.3 %), but in 24 (77.4 %) cases, it was performed in addition to extended resections. Other procedures in the study patients include segmentectomy in 17, bisegmentectomy in 19, trisegmentectomy in 17, right or left hepatectomy in 8, and extended right/left hepatectomy in 3. The mean (+/- SD) operation time was 241.7 +/- 78.2 min. The median amount of bleeding was 300 cc (range 25-2500), and 23 (32.4 %) cases required perioperative transfusion. The median hospitalization period was 5 days (range 1-47). Lengthened drainage (n = 9, 12.7 %) and intraabdominal abscess (n = 8, 11.23 %) were the most common problems. Hepatic resections using the HabibA (R) device seem to be feasible in cases with primary and metastatic hepatic lesions and benign liver masses and even those with hepatic trauma. It may lessen the amount of intraoperative hemorrhage, although lengthened drainage and intraabdominal abscess were the major postoperative problems in these cases.
WOS: 000367103500006
PubMed ID: 26702234
Keywords: Habib; Radiofrequency Device; Hepatectomy; Liver Surgery; Blood Loss